Twohop: Metric-based trust evaluation for peer-to-peer collaboration environments - ARGYROUDIS, PATROKLOS; O'MAHONY, DONAL EDWARD (IEEE, 2008)
Communications are increasingly relying on peer-to-peer models of interaction in which all participating entities have the same level of authority. Such models allow developed systems to overcome single points of failure, since there is no central management of security parameters. In order to select trustworthy service providers, peers in such environments require collaborative metrics that build trust relationships based on evidence of previous interactions. In this paper, we present a collaborative metric and an algorithm for the evaluation of trust in peer-to-peer networks called TwoHop. Our proposal requires no central management and scales to accommodate the fundamental need for growth that characterises peer-to-peer systems. Our experimental analysis and simulation results indicate the robustness of our design against dishonest participants and its ability to flexibly accommodate the needs of majorities.
PUBLISHED
Keywords: TwoHop peer-to-peer network failure recovery metric-based trust evaluation peer-to-peer collaboration environment trustworthy service provider